In vivo evaluation of a 1-piece foldable sutureless intrascleral fixation intraocular lens using ultrasound biomicroscopy and anterior segment OCT. Issue 3 (March 2021) - Mularoni, Alessandro; Imburgia, Aurelio; Forlini, Matteo; Rania, Laura; Possati, Giovanna Linda
Abstract : Evaluation of the optic plate, haptics position, and intrascleral haptic plugs of a new secondary IOL specially designed for the sutureless intrascleral fixation technique. Abstract : Purpose: To evaluate the optic plate and haptics of a specially designed sutureless intrascleral-fixated intraocular lens (IOL) using ultrasound biomicroscopy and anterior segment optical coherence tomography (AS-OCT). Setting: Department of Ophthalmology, San Marino Hospital, Republic of San Marino. Design: Retrospective observational case series. Methods: Eyes that underwent intrascleral fixation with IOL implantation (Carlevale) were included. Preoperative and postoperative refractive outcomes were reported. Optic plate tilt and haptics position were assessed with ultrasound biomicroscopy, whereas intrascleral plug depth and conformation were evaluated with AS-OCT. Results: The study comprised 10 aphakic eyes. Postoperative visual acuity improved in all patients. At postoperative month 3, 3 eyes (30%) had a vertical tilt of more than 100 μm, whereas no horizontal tilt was observed in any patient. The mean vertical intraocular tilt was 0.19 ± 0.22 mm. Of 20 haptics, 13 (65%) passed through the ciliary sulcus, 4 (20%) posterior to the ciliary body, and 3 (15%) through the ciliary body. AS-OCT scans showed a mean intrascleral plug depth of 247.20 ± 62.82 μm in the nasal sector and 265.50 ± 30.11 μm in the temporal sector, with adequate integration of the T-shaped plugs in the scleral tissue. Conclusions: This secondary IOL showed good intraocular stability and safe haptics fixation, making it suitable for the intrascleral fixation technique. The specific foldable design results in a low predisposition to optic plate tilt and haptic torsion. In long eyes, the sulcus-to-sulcus distance should be carefully evaluated preoperatively because the flexible structure of the IOL could be subjected to excessive stretching.